Penentuan Faktor Prioritas dalam Pemilihan Moda Transportasi Penumpang Rute Medan-Pematangsiantar dengan Menggunakan Metode Fuzzy-AHP dan Topsis - Butar, Pelixman Butar; Febrian, Didi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to help Unimed students determine priority modes of passenger transportation that suit the needs and capabilities of the community for the Medan-Pematangsiantar route. This research uses the Fuzzy-AHP and Topsis methods. The research results reveal that cost criteria have the greatest influence in choosing a mode of transportation, while safety criteria have the smallest influence. Apart from that, the most popular mode of transportation is buses, while the least popular is travel agents.